The Effect of Strain, Affect, and Personal/Social Resources on Problem Substance Use among Incarcerated and Non-Incarcerated Youth. Issue 10 (2nd October 2020) - Franco, Konrad; Grattet, Ryken
ABSTRACT: We explore the applicability of General Strain Theory to juvenile substance use. In doing so, we offer three advances over prior work. First, we put forward the concept of "problem substance use" to move beyond frequency-based and more medicalized conceptions of the phenomenon toward a conceptualization that views substance use as problematic when it disrupts social relationships and expectations and when it reflects a loss of self-control. Second, we employ a dataset that permits us to explore how strains originating in different life domains influence problem substance use as well as how negative emotions and personal coping resources mediate the relationship between strain and problem substance use. Third, we move beyond prior work by comparing how strain and strain mediators operate differently in schools, alternative learning centers, and juvenile correctional facilities. We find strong effects of the strain variables and strain mediators indicated by General Strain Theory and evidence that alternative learning centers and juvenile correction facilities are associated with especially high odds of problem substance use even when strain and other variables are controlled. We conclude by discussing the limitations of current work and the implications for next steps in the strain-substance use research literature.